Dual-field modular multiplier using Kogge-Stone adder - Yang Danyang (Dianzi Jishu Yingyong, 2019)
As the key operation, modular multiplication is the highest frequency of use in elliptic curve cryptography algorithm. Improving its operation speed is great significant to improve the performance of elliptic curve cryptography processor. Based on Kogge-Stone add structure, and combined with reconfigurable technology, this paper implemented a modular multiplier which support the operation in both prime field GF(p) and finite field GF(2m). And this modular multiplier reuse logic unit reasonably to save hardware resources. The modular multiplier was described by Verilog VHDL, and integrated in CMOS 0.18 μm technology library. The experimental results show that the maximum clock frequency of this modular multiplier circuit is about 476 MHz and use about 66 518 gates of hardware resources. The 256 bit Dual-field modular multiplication can be finished in 0.27 μs.